2018
DOI: 10.1002/jee.20191
|View full text |Cite
|
Sign up to set email alerts
|

Zooming Out from the Struggling Individual Student: An Account of the Cultural Construction of Engineering Ability in an Undergraduate Programming Class

Abstract: Background To explain educational problems such as student attrition, engineering education literature often focuses on the characteristics of individuals. In 2006, Ray McDermott and Hervé Varenne called for examining the “cultural construction” of educational problems, uncovering how multiple actors create and inscribe meaning to the educational problem. Purpose We apply the cultural construction framework to examine how the educational problem of a student being “not cut out for engineering” is constructed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 53 publications
(72 reference statements)
0
61
0
Order By: Relevance
“…Prior research has documented how this oppression emerges in interpersonal interactions and subconsciously becomes embedded within departmental cultures (e.g., Refs. [111][112][113][114]).…”
Section: Components Of This Principlementioning
confidence: 99%
“…Prior research has documented how this oppression emerges in interpersonal interactions and subconsciously becomes embedded within departmental cultures (e.g., Refs. [111][112][113][114]).…”
Section: Components Of This Principlementioning
confidence: 99%
“…Those papers under the "qualitative advanced" category used phenomenological (2), ethnography (2), lexical analysis, narrative method (1), critical theory (2), collaborative inquiry (1) for analysis. In particular, the novelty in using qualitative methods in EER was exemplified by one study [12], which drew upon critical theory and the narrative approach to examine the marginalized educational experiences of a female undergrad engineering student through one longitudinal interview. The large proportion of published qualitative studies and particularly the inclusion of research conducted in paradigms other than (post)positivism suggest that the JEE is in a process of shifting away from the dominance of positivist quantitative research in its publications.…”
Section: Jee Articlesmentioning
confidence: 99%
“…In higher STEM education, Kevin O'Connor has examined the ways particular institutional trajectories, instructor discourse, and course culture contribute to constructing categories of "Calculus-ready" [47,48]. Secules investigated the cultural construction of "not cut out for" engineering in an introductory programming course for electrical engineers [8]. Many of these studies make important insights about the subtle and unintended impacts of culture on students, even in courses with evidencebased pedagogy and well-intentioned instructors.…”
Section: Strengths and Critiques Of Cultural Scholarship On Inequitymentioning
confidence: 99%
“…Secules approached this limitation once the study concluded by making practical recommendations to the collaborator instructor and to readers [8]. Rather than leveraging critiques only against broad culture, specific classroom practices that recreate broad culture for the local setting are identified and shifted.…”
Section: Strengths and Critiques Of Cultural Scholarship On Inequitymentioning
confidence: 99%
See 1 more Smart Citation